Conceptual Changes of Fifth Graders towards Water Properties Concept in Mixed Materials through The Implementation of Predict-Observe-Explain Strategy Assisted by Science Kits - Sobariah, Isti; Suhandi, Andi; Sopandi, Wahyu (International Conference on Elementary Education, 2020)
The observation resulted that most elementary school students have misconceptions regarding the concept of water properties. A strategy which can be used to change the conception of elementary school students toward scientific conception is Predict-Observe-Explain (POE). This study aims to describe the level of conceptual change of fifth graders related to the concept of the water properties as an effect of applying the POE strategy-assisted science kit in learning. The method used was pre-experiment with one group pretest-posttest design on 38 fifth graders of an elementary school in Cileunyi District, Bandung Regency, West Java. The conceptions of fifth graders through POE strategy about concept of water properties identified by diagnostic test in the four-tier test (FTT) format. The results showed that the percentage of conceptual change of students consists of 1) early scientific conception (KISA) about 2.63%; 2) Static (S) around 23.68%; 3) Reconstruction (R) about 28.95%; 4) Construction (K) around 23.68%; and 5) Disorientation (D) around 21.06%. It can be concluded that the implementation of the POE strategy-assisted science kit in science learning materials for fifth graders has moderate effectiveness in facilitating the construction and the reconstruction level of elementary students' conceptions related to the concept of water properties